The Press and South Africa's Foreign Relations - Koos van Wyk (Communicare)
By using events data, the Afrikaans and English press has been compared for the comprehensiveness of their news coverage of South Africa's foreign relations. Events related to South Africa both as actor and target of foreign policy behaviour have been included. The findings show in broad terms that the Afrikaans press has been more comprehensive in reporting events where South Africa has been the actor. On the other hand, the English press has been far superior in their reporting events where South Africa has been the target of behaviour (external environment). These findings confirm the pluralistic nature of the press in South Africa, although some hegemonic features have been noticeable.